Pengaplikasian Internet Of Things (Iot) Pada Kran Air Sebagai Upaya Meminimalisir Interaksi Personal Hygiene - Parawangsa, Junior; Fita Lestari, Riska (Fakultas Teknik, Universitas PGRI Banyuwangi, 2022)
Absract - In the use of water faucets, we often cannot avoid interaction. The application of the internet of things on water faucets is an effort to minimize interactions when doing personal hygiene. This IOT-based water faucet mechanism utilizes body sensors, so that when someone approaches the faucet, the water will automatically come out without having to be rotated first. This innovation also supports efforts to implement health protocols during the Covid-19 pandemic. Keywords – Internet of Things (IoT); Interaction; Water Faucets; Pandemic Covid 19; Personal Hygiene.